Investigating the Benefits of Integrated Anatomy Instruction: A Cognitive Load Theory Perspective - Saiful Bahri, Talip; Zul Izhar, Mohd Ismail; Hadie, Siti Nurma Hanim (Penerbit Universiti Sains Malaysia and Malaysian Association of Education in Medicine and Health Sciences (MAEMHS), 2021)
Declining anatomy knowledge of junior doctors has been linked to clinical error judgement and medicolegal litigation. To overcome the problem, anatomy educators have introduced many teaching initiatives during undergraduate study that might promote anatomy knowledge acquisition and retention, including anatomy teaching using integrated instruction. Anatomy instruction can be integrated in terms of its contents and teaching approach. Learning from integrated anatomy instruction allows students to relate anatomy subjects with different subdisciplines and to comprehend related clinical context for future application. On the other hand, the integrated approach for anatomy teaching caters to different types of learning styles, therefore ensuring optimal learning. Nevertheless, causal relationships between integrated anatomy instruction and student learning has never been explicitly explored. Hence, this article aims to unearth the elements of integrated anatomy teaching that promote learning through instructional design theory, namely, cognitive load theory (CLT).